Improving Integrated Reporting Quality Through Islamic Corporate Governance - Yusvita Nena Arinta; M. Fatkhan Ashari (Universitas Mercu Buana, 2022)
Innovative and adaptive to face new business challenges by making the process of creating added value for the company. Integrated Reporting is a reflection of the efficiency and effectiveness of various types of corporate capital. The main focus of the implementation of integrated reporting is on transparency and optimizing stakeholder interests, namely in the field of corporate governance. This study aims to examine the effect of the implementation of the Islamic corporate governance mechanism on integrated reporting. The sampling in this study was purposive sampling with the results of 12 Islamic banks. Hypothesis testing using multiple regression analysis. The result of hypothesis testing is the characteristics of independent commissioners consisting of the number and frequency of audit committee meetings have a positive and significant effect on improving the quality of integrated reporting. characteristics of the audit committee consisting of the number of audit committees, audit committee education, and the frequency of audit committee meetings have a significant effect on increasing integrated reporting quality. sharia supervisory board consisting of the number, education and frequency of sharia supervisory board meetings have an effect on increasing integrated reporting quality, except for the variable number of sharia supervisory boards